Visible‐Light/Photoredox‐Mediated sp3 CH Functionalization and Coupling of Secondary Amines with Vinyl Azides in Flow Microreactors. Issue 2 (4th December 2015) - Tiwari, Dharmendra Kumar; Maurya, Ram Awatar; Nanubolu, Jagadeesh Babu
Abstract: Structurally diverse imidazole derivatives were synthesized by a visible‐light/[Ru(bpy)3 ][(PF6 )2 ]‐mediated coupling of vinyl azides and secondary amines in flow microreactors. This operationally simple and atom‐economical protocol allows the formation of three new CN bonds through the functionalization of sp 3 CH bonds adjacent to the secondary nitrogen atom. In order to get mechanistic insight of the coupling reaction, several control experiments were carried out and discussed. Abstract : Visibility that matters! A synthetic strategy for structurally diverse imidazoles that relies on visible‐light/[Ru(bpy)3 ][PF6 ]2 ‐mediated coupling of vinyl azides and secondary amines has been developed (see scheme; TBHP= tert ‐butyl hydroperoxide). This operationally simple and atom‐economical protocol allows the formation of three new CN bonds through the functionalization of sp 3 CH bonds.